INTEGRASI AGAMA DAN NEGARA DALAM PRODUK HUKUM PERKAWINAN PERSPEKTIF NEGARA HUKUM INDONESIA - Budiarti Budiarti (Zawiyah: Jurnal Pemikiran Islam, 2016)
According to the constitution, UUDNRI 1945, that religion and state have a relationship that is integral in determining the validity of a marriage in Indonesia. Religion is the foundation of the validity of a marriage, and the state gives legitimacy. Administrative toward marriage conducted according to the laws of each religion. Therefore, interfaith marriage is not a form of expression and religious freedom are guaranteed in the Constitution as a state of law that is based upon Almighty God. The implementation marital law product is not providing the legitimacy of marriage through a civil registry administratively, it is not discriminated against and do not conflict with the rule of law in Indonesia. Religion and state in the context of Indonesian law has a strong relationship in the organization of state power, it is necessary to pay attention to religious values in the formulation of a legal product, either through legislation, regulations, and judicial.